Ten questions a sociological perspective - Charon, Joel M. 1939- (Wadsworth Cengage Learning, 2013)
From the Publisher: What does it mean to be human? Are human beings free? Why is there misery in the world? Ten Questions: A Sociological Perspective examines the philosophies of the classical sociologists such as Marx, Weber, Durkheim, Mead, and Berger and looks at how the field of sociology has approached these questions over the past 150 years.